2020
DOI: 10.1021/acsmacrolett.0c00211
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene-block-Polydimethylsiloxane as a Potential Silica Substitute for Polysiloxane Reinforcement

Abstract: Here we report microphase-separated poly(styrene-block-dimethylsiloxane) (PS-b-PDMS) as a reinforcing filler in PDMS thermosets that overcomes the long-standing problem of aging in the processing of silicareinforced silicone. Surprisingly, PS-b-PDMS reinforced composites display comparable mechanical performance to silica-modified analogs, even though the modulus of PS is much smaller than that of silica and there is no evidence of percolation with respect to the rigid PS domains. We have found that a few uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…The cross-linkable PDMS matrix content is kept near 50 wt %, corresponding to the optimized diBCP/PDMS composition we identified previously. 34 Since the PDMS blocks in the diBCP and triBCP do not participate in the platinum-catalyzed cross-linking reaction, an insufficient cross-linkable PDMS matrix content impairs the mechanical properties. We first investigated the compatibilizing effect of the diBCP by the comparison between D50 and H34 D15.…”
Section: Acs Applied Polymer Materialsmentioning
confidence: 99%
“…The cross-linkable PDMS matrix content is kept near 50 wt %, corresponding to the optimized diBCP/PDMS composition we identified previously. 34 Since the PDMS blocks in the diBCP and triBCP do not participate in the platinum-catalyzed cross-linking reaction, an insufficient cross-linkable PDMS matrix content impairs the mechanical properties. We first investigated the compatibilizing effect of the diBCP by the comparison between D50 and H34 D15.…”
Section: Acs Applied Polymer Materialsmentioning
confidence: 99%
“…These findings demonstrate that the breadth of the compositional interface between the two dissimilar polymers and the modulus of the neighboring domain are key factors controlling the T g (z) behavior, providing insight for related theoretical efforts in the field 1,8,13,14,29−34 into the control parameters responsible for this phenomenon. Characterization of the local properties near the interface of PS/PDMS, in particular, are relevant for a range of applications from mechanical reinforcement of polymers 19,20 to the buckling-based metrology used to measure the modulus of ultrathin glassy films. 35−37 Figure 1a illustrates the multilayer sample geometry assembled for the fluorescence measurements that places a 10−15 nm thick pyrene-labeled PS probe layer (M w = 672 kg/ mol, M w /M n = 1.3 and 1.4 mol % pyrene 16,17,27,38 ) at a known distance z from the PS/PDMS interface by changing the thickness z of a neat PS (M w = 1920 kg/mol, M w /M n = 1.26) spacer layer between the underlying PDMS and pyrene-probe layer.…”
mentioning
confidence: 99%
“…Studies on thin polymer films have demonstrated a host of property changes with decreasing film thickness attributed to interface effects, including polymer–polymer interfaces. The efficient design of multicomponent materials requires the understanding of how these interface effects perturb local properties. Glassy–rubbery interfaces between polymer domains impart material toughness and flexibility , and can be used to tune phononic transport . Although a range of different processing methods have been developed to create morphologies with sub-100 nm domain sizes, studies of simplified systems with a single interface can directly inform the underlying mechanisms behind such applications by mapping local properties as a function of distance from the interface.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PS‐ b ‐PDMS BCPs ( M n = 20 kDa, dispersity ( Ð ) = 1.10; M n = 144 kDa, Ð = 1.15) were synthesized by anionic polymerization. [ 29 ] PS‐ b ‐PDMS BCPs ( M n = 33 kDa, Ð = 1.10; M n = 60 kDa, Ð = 1.02) were purchased from Polymer Source, Inc. P(S‐ r ‐N 3 ) polymers ( M n = 2k, Ð = 1.08) were synthesized by living radical polymerization. [ 10 ] SDS, FeCl 3 , tetra‐butylammonium fluoride solution (1.0 m in tetrahydrofuran), formaldehyde dimethyl acetal (99%), 1, 2‐dichloroehtane (99%), H 2 PtCl 6 , ethanol (reagent alcohol, anhydrous), and Nafion ionomer (5 wt%) were purchased from Sigma Aldrich.…”
Section: Methodsmentioning
confidence: 99%